Accelerating tracer transport in FESOM-2 with GPU's - Gijs van den Oord; David Guibert; Alessio Sclocco; Erwan Raffin; Ben van Werkhoven; Natalya Rakowski; Nicolay Koldunov; Dmitry Sidorenko (Zenodo, 2022)
Within the ESiWACE-2 service on porting applications to pre-exascale machines, we have collaborated with theFESOM-2 team to accelerate parts of their model on GPU's.FESOM-2 is a finite-volume ocean and sea-ice model based on unstructured meshes. We have used the OpenACC programming model to speed up the transport of tracers inFESOM-2. In this talk, I will share the results of this effort, describe our collaboration with theFESOMteam and present some technical aspects of the implementation. Finally, I will iterate on the lessons learned and the road ahead forFESOM-2 towards exascale.